The features of acquired thrombotic thrombocytopenic purpura occurring at advanced age. Issue 187 (March 2020) - Agosti, Pasquale; Mancini, Ilaria; Artoni, Andrea; Ferrari, Barbara; Pontiggia, Silvia; Trisolini, Silvia Maria; Facchini, Luca; Peyvandi, Flora; ,
Abstract: Introduction: Acquired thrombotic thrombocytopenic purpura (aTTP) is a rare life-threatening thrombotic microangiopathy (TMA) affecting more frequently women of 30–50 years of age. There is scarce information on the clinical features of aTTP occurring in the elderly. Our goal was to evaluate the impact of an elderly-onset disease on the expression, severity and management of aTTP. Materials and methods: We performed a cross-sectional study of patients enrolled in the Milan TTP Registry (www.ttpdatabase.org ) after a first acute episode of aTTP from January 2002 to March 2018. The aTTP diagnosis was suspected on the basis of the presence of thrombocytopenia and microangiopathic hemolytic anemia with no alternative causes, and was confirmed centrally by a severe plasma deficiency of ADAMTS13 activity (<10%). Triggers, clinical manifestations, laboratory parameters, management and outcome of the first acute events of elderly-onset aTTP patients (≥65 years) were compared with those of younger patients. Results: Among 143 eligible patients, 16 (11%) were elderly at onset. In comparison with younger cases they showed a lower rate of bleeding symptoms and severe anemia (30% and 18%), with a trend towards a higher rate of neurological and renal signs and symptoms. These patients were less frequently treated with plasma exchange and corticosteroids and more often with plasma infusion. No difference for gender, triggers and episode outcomes was observed. Conclusions: Older patients with aTTP differed from younger patients mainly for being treated less frequently with plasma exchange and corticosteroids, perhaps for the perceived risks associated with these treatments in the elderly.